2020
DOI: 10.3390/polym12030550
|View full text |Cite
|
Sign up to set email alerts
|

Post-Processing of FDM 3D-Printed Polylactic Acid Parts by Laser Beam Cutting

Abstract: In this paper, the post-processing of 3D-printed poly lactic acid (PLA) parts is investigated. Workpieces are manufactured by fused deposition modeling (FDM) 3D printing, while they may have defects in some areas such as edges. A post-processing is introduced here for 3D-printed samples by low power CO2 laser. The thickness of the FDM samples are 3.2 mm and printed by optimum conditions. Effects of process parameters such as focal plane position (−3.2–3.2 mm), laser power (20–40 W), and laser cutting speed (1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…By a few experiments, it has been identified that, compared to PLA, the surface smoothness in ABS does not increase. Hence, this method is more suitable for PLA print parts [ 232 , 233 , 234 ]. As per Lambiase et al’s [ 235 ] study, which was conducted with a 30 W power laser, when the laser paths overlapped, the surface became much smoother without generating any parallel grooves.…”
Section: Treatment Methods To Overcome or Minimize The Defects In mentioning
confidence: 99%
“…By a few experiments, it has been identified that, compared to PLA, the surface smoothness in ABS does not increase. Hence, this method is more suitable for PLA print parts [ 232 , 233 , 234 ]. As per Lambiase et al’s [ 235 ] study, which was conducted with a 30 W power laser, when the laser paths overlapped, the surface became much smoother without generating any parallel grooves.…”
Section: Treatment Methods To Overcome or Minimize The Defects In mentioning
confidence: 99%
“…RSM is based on applied mathematics and the statistical techniques to determine functional relationships between output responses which are affected by input factors [17]. RSM generates an empirical polynomial model of approximation for response surface over a factor region [18]. The smaller the region of interest, the better the approximation.…”
Section: Response Surface Methodology and Ann-gamentioning
confidence: 99%
“…In recent years, three-dimensional (3D) bioprinting has occupied a prominent place among all other methods for producing tissue scaffolds to bridge the divergence between artificially engineered tissue constructs and native tissues [10][11][12]. Due to increasingly emerging interests, its global market, which was estimated at nearly $ 487 million in 2014, is foreseen to reach $ 1.82 billion in 2022 [13].…”
Section: Introductionmentioning
confidence: 99%